Gas Emission of Palm Oil Waste Bricks During Firing Process at Different Heating Rates - Sarani, Noor Amira; Kadir, Aeslina Abdul; Othman, Hamidah Syd (International Journal of Engineering and Technology, 2018)
The demand for brick materials is expected to increase rapidly. However, pollutant emission during the firing process becomes a threat to the human and environment. Therefore, this study is focusing on the release of pollutant gasses during firing manufactured bricks. The bricks were incorporated with 5% of palm oil waste (palm kernel shell and empty fruit bunches) and fired at different heating rates: 1°C/min, 3°C/min and 5°C/min. All samples were fired until it reached 1050°C and retained for 2 hours soaking time. The gas emission measured during firing process includes carbon monoxide (CO), carbon dioxide (CO2), nitrogen oxide (NO) and sulfur dioxide (SO2). The results of estimated total emission (ETE) of gasses were compared to control bricks and palm oil waste brick. The result obtained has shown that increased heating rates cause decreased in gas emission, especially for CO2 and CO. Therefore, this study determined that pollutant gasses are least minimal at high heating rates (5°C/min). As a conclusion, several pollutant gasses did not comply with the federal Clean Air Act’s National Ambient Air Quality Standard (NAAQS) set by Environmental Protection Agency.